Strategi Pengembangan Kompetensi Mahasantriwati: Studi Mahasantri Ma’had Al-Jami’ah Kampus 1 Institut Agama Islam Negeri Sultan Amai Gorontalo - Supiah, Supiah; Paus, Juldus R (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2020)
This study aims to investigate the efforts of Ma'had Al-Jami'ah of AIN Sultan Amai Gorontalo in exploring and developing mahasantriwati's competencies. This field research employed descriptive qualitative methods through primary and secondary data sources. The data collection techniques employed in this study were observation, interview, and documentation. The results of the study showed that the effort in developing mahasantriwati's competencies was manifested in such superior programs, namely curriculum and learning method development program; human resources, syllabus, and institutional development program; academic potential development program; language competency development program; and skills development program.